- KAJIAN KRIMINOLOGI TERHADAP TERPIDANA NARKOTIKA SEBAGAI PENYEBAB OVER KAPASITAS DI LEMBAGA PEMASYARAKATAN: Analisis Faktor Kriminogenik, Dampak Sistem Peradilan Pidana, dan Rekomendasi Reformasi Kebijakan Lapas di Indonesia - Patrecia Simamora; Anastasya Hutapea; Petrus Panjaitan (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2026)
This article analyzes Indonesia's criminal law policy regarding Narcotics Crimes, particularly reviewed from the perspective of Law Number 35 of 2009. The primary objective of this paper is to identify the factors contributing to the dominance of narcotics cases in Correctional Institutions (Lembaga Pemasyarakatan or Lapas) and to measure the significant impact of severe and long-term prison sentences on the issue of Lapas overcrowding in Indonesia. The methodology employed is normative legal research using statutory and conceptual approaches. The findings indicate that the emphasis on incarceration for all categories of perpetrators (especially users and low-level dealers) without strong differentiation, coupled with the application of high minimum penalties, is the primary driver of overcrowding. The conclusion underscores the need for sentencing policy reform, such as maximizing rehabilitation for addicts and considering non-custodial alternative sanctions to alleviate the capacity burden on Indonesia's Correctional Institutions.